(3GdMLI Ydi Cgd GdeOjfIs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s ((3YHO GdbGOQ Hf eMeO ShjQL s)
(3ChdgG (B:s
(3jHOC HHGH ENJdGa Cgd GdchaI hCgd GdeOjfI ai GdUdGI hGdehGbjJ s
(3BNQgG (B:s
(3hbGd CHh MfjaI hef bGd Hbhdg GdLhGhdi HGdejQGK ef GdGN hef GdGH hGdGe bGd jG Hfi GOe hgh bhd CHj HcQ GdUOjb QVi Gddg JYGdi Yfg hYf LejY GdUMGHI CLejYf Je GdcJGH GdeSei HGdMLI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs